A solid phase extraction based non-disruptive sampling technique to investigate the surface chemistry of macroalgae. Issue 2 (7th February 2016) - Cirri, Emilio; Grosser, Katharina; Pohnert, Georg
Abstract : The surface chemistry of aquatic organisms determines their biotic interactions. Metabolites in the spatially limited laminar boundary layer mediate processes, such as antifouling, allelopathy and chemical defense against herbivores. However, very few methods are available for the investigation of such surface metabolites. An approach is described in which surfaces are extracted by means of C18 solid phase material. By powdering wet algal surfaces with this material, organic compounds are adsorbed and can be easily recovered for subsequent liquid chromatography/mass spectrometry (LC/MS) and gas chromatography/mass spectrometry (GC/MS) investigations. The method is robust, picks up metabolites of a broad polarity range and is easy to handle. It is more universal compared to established solvent dipping protocols and it does not cause damage to the test organisms. A protocol is introduced for the macroalgae Fucus vesiculosus, Caulerpa taxifolia and Gracilaria vermiculophylla, but it can be easily transferred to other aquatic organisms.